Optimalisasi Kualitas Pendidikan Melalui Metode Keteladanan Dalam Tradisi Pendidikan Islam - Meri Safitri (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This article discusses how the exemplary method in Islam can be used to improve the quality of education. The exemplary method means that educators provide good examples to students. Not just giving lectures to students. This study uses a literature study, namely by reading and analyzing various sources that have been mentioned in the method that discusses Islamic education and this method. The results of the study show that this method is very suitable for forming the character and morals of students. Because they tend to imitate what they see. This exemplary is in accordance with the verses of the Koran, namely the letter Al-Ahzab: 21 and also the letter Luqman verse 17. Where in the letter Al-Azab it is stated that the Prophet Muhammad is the best example. However, in reality, in today's education there are still many educators who have not implemented this exemplary method consistently. There are several challenges, such as the lack of cooperation between schools and parents and also the lack of training for teachers and the influence of the external environment. Therefore, cooperation is needed from schools, families, and also the community to practice the exemplary method again. In this way, Islamic education can produce students who are not only cognitively intelligent, but also have good morals.